Reengineering REST API Monolit ke Microservice Menggunakan Framework Laravel - Sahrudin, Asep; Adriansyah, Ahmad Rio (DBESTI: Journal of Digital Business and Technology Innovation, 2025)
The increasing population growth in Jakarta has also led to a surge in demand for housing, including boarding houses. This surge in demand has become a challenge in managing applications and websites that provide information and services related to boarding houses, particularly in terms of managing user activity within the system. Therefore, researchers are trying to restructure the existing boarding house application using a microservice model. This research discusses the restructuring of the backend application from a monolithic to a microservice model, with a case study on Kos Jenggot. The development method employed in this research is Extreme Programming (XP), which incorporates testing methods, including black-box and performance testing. The results of this research show that using the microservice model is superior to the monolithic model; with black box testing results of 100%, the feature can run well through performance for the most significant scenario, namely an access load of 200 users in 100 seconds which has a total error of 100% for the monolithic model and 40 % for microservice models. These results indicate that the microservice model is more effective than the monolithic model for restructuring boarding applications.